Trade-offs in fishing strategy decisions and conservation implications for small-scale fisheries - Wade, Eric; Biedenweg, Kelly (Environmental Conservation, 2024)
People are psychologically predisposed to minimize their losses, even in the face of substantial gains. This predisposition, referred to as ‘loss aversion’, is especially present when people face uncertain outcomes. In small-scale fisheries, where fishers’ decisions are influenced by monetary and non-monetary assets, exploring how loss aversion intersects with conservation efforts may offer insights into how fishers balance short-term and long-term priorities. This study assessed the variables that contribute to loss aversion of small-scale fishers when making trade-offs between two valued assets: information-sharing and catch success. We used a structured questionnaire and a hypothetical simple lottery choice task of 78 fishers across 20 fishing beaches in Jamaica. We found that fishers were marginally more loss averse when both information-sharing opportunities and catch success were threatened than when only catch success was threatened. Communication frequency and size of fishing crew contributed significantly to fishers’ loss aversion in most choice sets, regardless of whether materially or non-materially valued assets were threatened. By exploring the drivers underpinning fishers’ choices, we provide insights into how the consideration of these variables can support the development of fisheries conservation measures that better align with the decision priorities of fishers.
Keywords: Jamaica; loss aversion; monetary assets; non-monetary assets; small-scale fisheries